Personnel management of organizations (on the example of LLC "Silpo-Food") - Hurzhii, Nataliia; Bateruk, Miroslav (Management and Entrepreneurship: Trends of Development, 2025)
The purpose of the article is to identify specific problems and develop recommendations for the stable functioning and development of the company in crisis conditions. The study is based on theoretical and practical aspects of improving personnel management in retail trade, using the example of LLC Silpo-Food, taking into account the impact of a full-scale war. The article analyzes the scientific literature and practice of personnel management in Silpo-Food. A comprehensive approach is applied, including a description of the organizational structure, analysis of personnel policy and assessment of the impact of the war. Methods of analysis, synthesis, comparison and generalization are used. Categories of managers, personnel, mobility, personnel policy, functions of the personnel department are considered. The structure, values and personnel management system of Silpo-Food in war conditions are analyzed. The originality of the article lies in the study of the impact of a full-scale war on the personnel policy of a Ukrainian retail enterprise, which is new to the scientific literature. A comprehensive approach is applied, combining theory with practice, to assess the effectiveness of personnel management in war conditions. Special attention is paid to adapting personnel policy to changing circumstances to ensure business sustainability. The value of the study lies in its practical, scientific and social significance. From a practical point of view, the results are useful for the management of Silpo-Food and other retail enterprises, suggesting ways to retain and motivate staff, adapt to new forms of work, ensure safety and psychological support. From a scientific point of view, the study contributes to the theory of personnel management in the context of crisis situations and military conflicts, expanding the understanding of effective human capital management. The social significance lies in emphasizing the importance of social responsibility of business in a crisis, preserving jobs and supporting employees. Therefore, effective personnel management is critically important, especially in crisis conditions. JEL Classification: J5, J6, M1, M5